Productive behavior of piglets (Sus scrofa domesticus) fed concentrates with an inclusion of six natural flavorings and one commercial synthetic flavoring (Agroindustrial Science, 2024)
Natural additives can provide positive characteristics that help make animal feed more palatable, thereby increasing feed intake and improving productivity. In this study, 260 piglets from 14 to 56 days of age were monitored, with an initial weight of 4.34 ± 0.75 kilograms. There were 6 treatments with natural flavorings with pro-nutrients, plus 1 treatment with a commercial product, and 1 control without flavorings. The average daily feed consumption per piglet was between 408 and 525 g, the average final weights between 19.90 and 26.30 kg, the average daily weight gains between 0.367 and 0.517, and the average feed conversions were between 0.988 and 1.195. Feeding costs averaged between 0.78 and 0.94 dollars. It was observed that the best values for live weight gain and feed conversion index, and decreasing production costs, were for treatments that included natural flavorings. It is recommended to study the use of these aromas in the growth and fattening stages.
Keywords: Flavoring; Non-nutritional additive; Piglet; Productive behavior